Epidemiological study of road traffic accident cases in Greater Noida: Hospital Based Study - Roy, Rupali; Chaturvedi, Manish; Katiyar, Kalpana; Agrawal, Deepika (Indian Journal of Community Health, 2014)
Introduction: Road accidents are associated with numerous problems each of which needs to be addressed separately [1]. Accidents, therefore, can be studied in terms of agent, host and environmental factors and epidemiologically classified into time, place and person distribution [2]. Objectives: 1.To assess the prevalence of RTAs coming to hospital and 2.To know the epidemiological factors related to RTAs and associated prevalence in hospital based study. Methodology: This cross sectional study was conducted at SMSR, Gr Noida, in 2012. The study group consisted of all the RTA victims reporting to casualty in the last one year. The victims of the accidents were interviewed on a pretested semi structured performa. Results: In that one year period total number of reported accident cases was 144. The age groups of the study subjects were between 13-65 years. Out of total study subjects, only 16 were female. Again out of the total accident cases 45% were attended by police and of all injured, 45.8% were driver by occupation (7% without driving license). Among these drivers, 11% were not attentive during driving because of various reasons. Ambulance services had reached in 46.5% cases. Fracture was the most common type (60%) of injury among all types of injuries. Among the applicable population only 33% wore helmet or seat belts. Conclusions: Only half of the total accident cases were attended by police and again only half of them received ambulance services. One third injuries were because of not wearing seat belt and helmets.